Applying the FDS pyrolysis model to predict heat release rate in small-scale forced ventilation tunnel experiments. (March 2020) - Wang, Xiaoyun; Fleischmann, Charles; Spearpoint, Michael
Abstract: The pyrolysis model in FDS6 is applied to simulate a series of small-scale tunnel experiments under varied forced ventilation velocities, where cribs made of medium density fireboard (MDF) are used as the fuel source. Prior to the simulations the material properties of MDF are investigated in order to effectively describe the decomposition behaviour in FDS6 and to develop optimised values. In the tunnel simulations, the effect of the burning duration of the ignition source, the heat of combustion of the MDF in the presence of the forced ventilation, the assumed fuel mass and the modelling domain set-up on the prediction of heat release rate are examined. It is found that the cribs take longer to ignite than that in the experiment; the available burning mass is affected by the assumed thickness of the crib sticks and the available surface area; and a limited domain size can result in not all of the fuel burning. Efforts are made to obtain an equivalent burning mass to the experiments and to account for the influence of the forced ventilation on the burning efficiency by manually specifying the heat of combustion to improve the predictions of heat release rate and consumption of fuel mass.